Misled by Evgenii Khaldei: "Budapest Ghetto" Photos Staged outside the Ghetto and Their False Narratives - Pastor, Peter (Holocaust and genocide studies, 2022)
World War II Soviet photojournalist Evgenii Khaldei gained fame in the West when his photographs of war victims were exhibited there in the 1990s. Among his Holocaust-related images are two iconic photos that he claimed were taken upon the January 18, 1945 liberation of the Budapest ghetto. One represents the wanton murder of Jews, the other their survival. Exhibited or published, these photos were accompanied by Khaldei’s brief stories about their subjects. The following examination proves that they were not taken in the ghetto, that they were staged, and that the stories Khaldei attached to them were false.